Agents and artificial intelligence : 7th International Conference, ICAART 2015, Lisbon, Portugal, January 10-12, 2015, Revised selected papers /: 7th International Conference, ICAART 2015, Lisbon, Portugal, January 10-12, 2015, Revised selected papers. (2015) - Unknown
No abstract available